The Role of the Euro During and After Economical Crisis - Daniela MATEI (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2010)
The impact of the single currency on international capital markets has been one of the most abiding features of the euro’s historical development. In response to the global financial and economic crisis, governments across the world are sorting to creating national deficit levels on a virtually unprecedented scale to plug gaping holes in public finances and propel economies towards recovery. As a result, borrowing conditions on global capital markets are taking on not only an economic, but also an intensely political significance.